Composting and Agroecological Garden of UnAPI: An Alternative for Recycling Organic Waste at UFMS - Righi-Cavallaro, Karina Ocampo; Cury, Juliano de Carvalho; Costa, Joao Vitor; de Carvalho, Leonardo Chaves; Turine, Marcelo Augusto Santos; Itavo, Camila Celeste Brandao Ferreira (Universitas Diponegoro, 2024)
The composting process is an alternative for recycling organic waste, facilitated by microorganisms that produce compost or organic fertilizer in the presence of oxygen. The resulting compost can be used as fertilizer, significantly improving soil structure. The “Composta UFMS” project aims to environmentally manage organic solid waste generated on the UFMS University City campus in Campo Grande. Currently, dry leaves, pruning and weeding residues, wood shaving from vivarium, and organic waste from the University Restaurant are being directed for composting. In addition to valuing organic waste generated on the UFMS campus and used in the production of organic compost for the extension activities of the UnAPI Agroecological Garden project, the Biovalorization of Organic Waste project also includes scientific initiation subprojects, such as the study of growth potential of fungi of the genus Pleurotus on substrates derived from different organic residues and their mixtures for mushroom production. In addition to Environmental Education actions in schools with the Composting and Urban Agriculture in Schools project using the composting method directly on the soil, eliminating the need for turning. These actions resulted in the year 2023, the diversion of 4 tons of wood shavings from the vivarium and 4.8 tons of organic waste from the University Restaurant for composting, the care of around 60 elderly people in the UnAPI Agroecological Garden project and 5 schools in the Compostagem and Urban Agriculture in Schools. The results of this study will serve as a basis for the management of organic waste on the UFMS Campo Grande campus, as well as for future research on composting, as well as new Environmental Education and Scientific Dissemination actions.